Fractal analysis of tree paintings by Piet Mondrian (1872-1944). (2017) - Bountis, Tassos; Fokas, Athanassios S.; Psarakis, Emmanouil Z.
We examine two paintings by Piet Mondrian, and suggest that his depiction of tree foliages exhibit fractal patterns of a specific dimension. Our analysis implies that fractality may possess an aesthetic value that affected Mondrian, perhaps in a similar way as it inspired Jackson Pollock, another famous painter who incorporated fractality in several of his paintings. In recent years there has been a stimulating debate among scientists arguing for and against the thesis that Jackson Pollock's drip paintings when analysed at small scales can be described by the mathematics of fractal geometry. Our suggestion that fractal patterns exist in the paintings of a second famous artist - in this case Piet Mondrian - further supports the hypothesis that the beauty which exists in fractality may affect consciously or subconsciously such great painters as Jackson Pollock and Piet Mondrian.